Acceptability of the Quran Translation - Al Farisi, Mohamad Zaka (Al-Jami'ah Research Centre, 2023)
Muslims have regarded the translation of the Quran into languages other than Arabic as valuable since its benefits for non-Arabic speakers to understand the its messages. However, those translations are not a substitute for the original Arabic Quran, and reciting the Quran in Arabic is not the same as reading its translation. Linguistically, translation is a dual act of interlingual communication that involves the source language (SL), target language (TL), and translator as the main actor. The translator is in charge of presenting the acceptable equivalence of the SL text and the TL text, either on the levels of form, meaning, or intent. Therefore, the acceptability of the translation of Quranic verses is not related merely to their forms and meanings but also to the intended purpose of the text of the SL. In practice, the acceptability of translations can be realized, among other things, by applying appropriate translation techniques and procedures when handling micro-translation units, whether on word, phrase, clause, or sentence levels. In this regard, the acceptability of the Quran translation necessitates the fulfilment of the aspects of accuracy, clarity, naturalness, and relevance. These aspects will bring an acceptability model for a Quranic translation that considered complete and representative. This model stems from the view that translation is not merely seen from the point of communication theory of the code but also from the point of communication theory of inference model. [Umat Islam melihat terjemahan Al-Quran ke dalam bahasa selain bahasa Arab sebagai sesuatu yang berharga karena manfaatnya bagi penutur non-Arab untuk memahami pesan-pesannya. Namun, terjemahan tersebut sejajar dengan Al-Quran yang berbahasa Arab, sehingga membaca Al-Quran dalam bahasa Arab tidak dianggap sama dengan membaca terjemahnya. Secara linguistik, penerjemahan merupakan suatu tindakan komunikasi ganda antarbahasa yang melibatkan bahasa sumber (SL), bahasa sasaran (TL), dan penerjemah sebagai pelaku utama. Penerjemah bertugas menyajikan padanan teks SL dan teks TL yang dapat diterima, baik dalam tataran bentuk, makna, maupun maksudnya. Oleh karena itu, keterterimaan terjemahan ayat-ayat Al-Quran tidak semata-mata berkaitan dengan bentuk dan maknanya, tetapi juga dengan maksud teks tersebut. Dalam praktiknya, keterterimaan terjemah dapat diupayakan antara lain dengan menerapkan teknik dan prosedur penerjemahan yang tepat terkait dengan satuan terjemahan mikro, baik pada tataran kata, frasa, klausa, maupun kalimat. Dalam kaitan ini, akseptabilitas terjemah Al-Quran memerlukan pemenuhan aspek akurasi, kejelasan, kealamian, dan relevansi. Aspek-aspek tersebut akan melahirkan suatu model akseptabilitas suatu terjemah Al-Quran yang dapat dianggap lengkap dan representatif. Model seperti ini berdasarkan pada pandangan bahwa penerjemahan tidak hanya dilihat dari sudut teori komunikasi tentang kode tetapi juga dari sudut teori komunikasi tentang inferensi.]